Panduan Pelatihan dengan Strategi Belajar Terstruktur untuk Meningkatkan Disiplin Belajar Siswa SMA - Anis Tri Yuliana; Nur Hidayah; Carolina Ligya Radjah (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to produce products that have been tested by media experts learning and expert guidance and counselling. The design used in this study was the development of Borg & Gall (1983). Subjects of learning media experts are 2 people and guidance and counseling experts 2 people. The results of the assessment from learning media experts and expert guidance and counseling were analyzed with numerical data and non-numeric data. The final results of the assessment of learning media experts obtain a validity index of 0.94 with the category